Plasma C24:0- and C26:0-lysophosphatidylcholines are reliable biomarkers for the diagnosis of peroxisomal β-oxidation disorders - Blai Morales-Romero; José Manuel González de Aledo-Castillo; Cristina Fernández Sierra; Carmen Martínez Carreira; Carles Zaragoza Bonet; Rosa Fernández Bonifacio; Maria Antònia Caro Miró; Ana Argudo-Ramírez; Rosa María López Galera; Judit García-Villoria (Journal of Lipid Research, 2024)
The gold-standard diagnostic test for peroxisomal disorders (PDs) is plasma concentration analysis of very long-chain fatty acids (VLCFAs). However, this method’s time-consuming nature and limitations in cases which present normal VLCFA levels necessitates alternative approaches. The analysis of C26:0-lysophosphatydylcholine (C26:0-LPC) in dried blood spot samples by tandem-mass spectrometry (MS/MS) has successfully been implemented in certain newborn screening programs to diagnose X-linked adrenoleukodystrophy (ALD). However, the diagnostic potential of very long-chain LPCs concentrations in plasma remains poorly understood. This study sought to evaluate the diagnostic performance of C26:0-LPC and other very long-chain LPCs, comparing them to VLCFA analysis in plasma. The study, which included 330 individuals affected by a peroxisomal β-oxidation deficiency and 407 control individuals, revealed that C26:0- and C24:0-LPC concentrations demonstrated the highest diagnostic accuracy (98.8% and 98.4%, respectively), outperforming VLCFA when C26:0/C22:0 and C24:0/C22:0 ratios were combined (98.1%). Combining C24:0- and C26:0-LPC gave the highest sensitivity (99.7%), with ALD females exhibiting notably higher sensitivity compared with the VLCFA ratio combination (98.7% vs. 93.5%, respectively). In contrast, C22:0-LPC exhibited suboptimal performance, primarily due to its low sensitivity (75%), but we identified a potential use to help distinguish between ALD and Zellweger spectrum disorders. In summary, MS/MS analysis of plasma C24:0- and C26:0-LPC concentrations represents a rapid and straightforward approach to diagnose PDs, demonstrating superior diagnostic accuracy, particularly in ALD females, compared with conventional VLCFA biomarkers. We strongly recommend integrating very-long chain LPC plasma analysis in the diagnostic evaluation of individuals suspected of having a PD.